2024
DOI: 10.1038/s41598-024-52738-5
|View full text |Cite
|
Sign up to set email alerts
|

RARRES2 is involved in the “lock-and-key” interactions between osteosarcoma stem cells and tumor-associated macrophages

Jingjin Ma,
Zhiyu Chen,
Qiaochu Li
et al.

Abstract: Osteosarcoma (OS) is a type of tumor. Osteosarcoma stem cells (OSCs) are responsible for drug resistance, recurrence, and immunosuppression in OS. We aimed to determine the heterogeneity of OSCs and the immunosuppression mechanisms underlying the interactions between OSCs and tumor-associated macrophages (TAMs). The cell components, trajectory changes, and cell communication profiles of OS cells were analyzed by transcriptomics at the single-cell level. The intercellular communication patterns of OSCs were ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
1
0
0
Order By: Relevance
“…Similar results have been recently obtained in osteosarcoma, in which coculture experiments with TAMs and osteosarcoma cells indicate a critical role of TAM-produced IGF1 in osteosarcoma stemness [80]. In this study, the authors specifically demonstrated that TAM-secreted IGF1 acts on osteosarcoma cells and up-regulates RARRES2 expression, which maintains stemness through the NF-kB pathway and promotes chemotaxis of TAMs [80].…”
Section: The Igf System and Tumor-associated Macrophagessupporting
confidence: 86%
“…Similar results have been recently obtained in osteosarcoma, in which coculture experiments with TAMs and osteosarcoma cells indicate a critical role of TAM-produced IGF1 in osteosarcoma stemness [80]. In this study, the authors specifically demonstrated that TAM-secreted IGF1 acts on osteosarcoma cells and up-regulates RARRES2 expression, which maintains stemness through the NF-kB pathway and promotes chemotaxis of TAMs [80].…”
Section: The Igf System and Tumor-associated Macrophagessupporting
confidence: 86%